The GPS / EGNOS Positioning Quality in APV-1 and LPV-200 flight procedures - Grzegorz Grunwald; Adam Ciećko; Kamil Krasuski; Rafał Kaźmierczak (Communications - Scientific letters of the University of Zilina, 2021)
Accuracy, integrity, continuity and availability are the basic quality parameters extremely important in satellite navigation. The article presents results of research using the European Geostationary Navigation Overlay Service (EGNOS) that belongs to the group of Satellite Based Augmentation Systems (SBAS). The measurement data adopted for analysis were recorded in years: 2012, 2014, 2015, 2017 and 2018 in the north-eastern Poland. Results of the analysis showed a significant reduction in the maximum GPS / EGNOS positioning error values from 2014 onwards (compared to results from 2012). In general, values of parameters characterizing accuracy, integrity and availability meet the requirements for EGNOS applications in APV-1 and LPV-200 aviation procedures. It the case of continuity the requirements are not met.